Median arcuate ligament syndrome (Dunbar syndrome): A diagnosis not to be underestimated - Asma Sghaier, PhD; Mohamed Amine Jelassi; Khalil Fradi; Mohamed Hédi Mraidha; Fehmi Hamila; Sabri Youssef (Radiology Case Reports, 2024)
Medial arcuate ligament syndrome (MALS) is an anatomoclinical entity underestimated in most situations due to the lack of specific signs. However, the consequences can be disastrous if the diagnosis is not seriously considered and investigations are not fully undertaken to confirm this hypothesis. We report a case of Median Arcuate Ligament Syndrome in a young woman who presented to the Emergency Department with moderate postprandial pain. All investigations were carried out promptly, with no abnormalities, and the diagnosis was retained on the evidence of a well-performed and appropriately interpreted abdominal CT. This case illustrates a rare cause of epigastralgia simulating a surgical emergency. This condition should be considered when biological and often radiological investigations are inconclusive. The relative youth of the patient is often suggestive, but confirmation is based on a CT scan with injection of a well-technical contrast product, or angiography. Treatment is debatable between a conservative approach and surgery. Surgical approach is discussed depending on the degree of vascular stenosis and the impact on the digestive tract. However, the recurrence of symptoms may be a contributory factor in the therapeutic decision. The impact could be lethal depending on the degree of stenosis and consequently on the repercussions on the digestive tract. A multidisciplinary approach is required for its management.